Feasibility of the virtual reality-based assessments in patients with panic disorder - Kim, Byung-Hoon; Kim, Jae-Jin; Oh, Jooyoung; Kim, Seung-Hyun; Han, Changsu; Jeong, Hyun-Ghang; Lee, Moon-Soo; Kim, Junhyung (Frontiers in Psychiatry, 2023)
Introduction Recurrences and diagnostic instability of panic disorder (PD) are common and have a negative effect on its long-term course. Developing a novel assessment tool for anxiety that can be used in a multimodal approach may improve these problems in panic disorder patients. This study assessed the feasibility of virtual reality-based assessment in panic disorder (VRA-PD). Methods Twenty-five patients with PD (ANX group) and 28 healthy adults (CON group) participated in the study. VRA-PD consisted of four modules based on the key components of cognitive behavior therapy for an anxiety disorder: “Baseline evaluation module” (M0), “Daily environment exposure module” (M1), “Relaxation module” (M2), and “Interoceptive exposure module” (M3). Multiple evaluations, including self-rating anxiety scores (AS) and physiological responses [heart rate variability (HRV) index], were performed in three steps at M1, M2, and M3, and once at M0. Comparisons between patients with PD and healthy controls, factor analysis of variables in VRA-PD, changes in responses within modules, and correlation analysis between variables in VRA-PD and anxiety symptoms assessed by psychological scales were performed. Results All participants completed the VRA-PD without discontinuation. The ANX group reported significantly higher AS for all steps and a smaller HRV index in M1 (steps 1 and 2) and M2 (step 1). Repeated-measures analysis of covariance (ANCOVA) revealed significant interaction effects for AS in M1 (F = 4.09, p = 0.02) and M2 (F = 4.20, p = 0.02), and HRV index in M2 (F = 16.22, p < 0.001) and M3 (F = 21.22, p = 0.02). The HRV index only indicated a good model fit for the three-factor model, reflecting the construct of the VRA-PD. Both AS and HRV indexes were significantly correlated with anxiety and depression symptoms. Discussion The current study provides preliminary evidence that the VRA-PD could be a valid anxiety behavior assessment tool.